Polypharmacy Leading to Priapism in HIV Patient with Schizoaffective Disorder: A CYP450 Cascade - Vinod Sharma; Aditi Sharma (Case Reports in Psychiatry)
With increasing trend of polypharmacy, there are higher chances of drug-drug interactions leading to adverse effects, especially in psychiatric patients with co-morbid chronic medical problems. This case demonstrates a schizoaffective 30-year-old male on highly active antiretroviral therapy (HAART) who reported an incident of priapism potentially caused by an interaction between previously prescribed atypical antipsychotic, trazodone, norepinephrine dopamine reuptake inhibitor (NDRI), HAART, and newly added selective serotonin reuptake inhibitor (SSRI). This case emphasizes obtaining careful medication history, understanding cytochrome P450 (CYP450) enzyme and its subtypes, and discouraging polypharmacy. Clinicians must educate their patients about different sexual side effects as these can be socially stigmatizing and can further deteriorate mental health symptoms.